(untitled) (The Pakistan Development Review, 1970)
Many countries have "regional problems". Income and political power are allocated unequally among regions with no significant change over time, and these inequities are a source of political tension. The regional problem in Pakistan is especially severe because the peculiar geographic nature of Pakistan makes the issue so visible1. Economic planners in Pakistan and other poor countries are often as¬signed the task of designing programmes to bring about income parity among regions. In doing so, planners confront several analytic and technical prob¬lems. The principal difficulty is how to allocate resources so as to best conform to political preferences of policy-makers. In this context it is desirable to dis¬cover and exploit the comparative advantages of the regions. Regional com¬parative advantages, in turn, are dependent upon the regional distribution of resources and upon political preferences as to the regional allocation of welfare.